2016
DOI: 10.1080/19439962.2016.1173155
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the lighting system on the driver's behavior in road tunnels: A driving simulator study

Abstract: ACCEPTED MANUSCRIPTACCEPTED MANUSCRIPT 2 systems. This technology is spreading fast because of its low energy consumption and the high durability combined with low maintenance requirement. Aim of this research was to assess, by means of a driving simulator experimentation, the impact of the LED lighting system on traffic safety. The driver performance approaching, inside and exiting LED lighted tunnels was analysed and compared to the behaviour maintained in tunnels illuminated with a traditional system, in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…By means of driving simulator experimentation, Domenichini analysed the driving performance in Light-Emitting Diode (LED) lighted tunnels and High-Pressure Sodium (HPS) lighted tunnels, the results revealed that simulated LED lights often induced a better driving behaviour under some aspects (Domenichini et al 2017). However, the lighting system represents the most expensive operative cost of a tunnel.…”
Section: Introductionmentioning
confidence: 99%
“…By means of driving simulator experimentation, Domenichini analysed the driving performance in Light-Emitting Diode (LED) lighted tunnels and High-Pressure Sodium (HPS) lighted tunnels, the results revealed that simulated LED lights often induced a better driving behaviour under some aspects (Domenichini et al 2017). However, the lighting system represents the most expensive operative cost of a tunnel.…”
Section: Introductionmentioning
confidence: 99%
“…One limitation should be noted regarding this study's findings. Driving speed has been shown to significantly affect a driver's perceived distance; higher vehicle speeds result in lower perceived distances [17,23,24]. As such, drivers participating in this study's field experiments were required to drive at a speed of 60 km/h.…”
Section: Field Experimentmentioning
confidence: 99%
“…Some debate exists regarding the ability of driving simulators to accurately replicate driving experience and associated driver behavior in real tunnels. Select studies found that driver performance was similar in virtual and real environments [16][17][18], while other studies reported a significant difference in driver behavior in these two environments [19,20]. For example, driving speed was higher and vehicle distance to the nearest tunnel wall was much lower in simulated tunnels as compared with real tunnels.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the structural complexity and limited internal space, the environment within a tunnel is quite different from that on the open road. These features of tunnels were proved to cause increased visual mental workload 2 and stress 3 associated with lower driving speeds and differences in lateral deviations (distance to the tunnel wall). 4 In a dynamic visual environment, traffic information is obtained via various senses, and approximately 90% of the information is obtained through vision.…”
Section: Introductionmentioning
confidence: 99%